Digital Ethics: The Use of Social Media in Gen Z Glasses - Fauzan Abdillah; Guruh Marhaenis Handoko Putro (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
This study is about digital ethics among Generation Z in the city of Surabaya, facing the era of digitalization and society 5.0 with various challenges on various social media platforms, so that it is expected to be more ethical, optimal and safe. One of the objectives of this study is to determine the response of Generation Z toward hoax information by using generation z digital literacy skills and digital ethics owned by generation z in the city of Surabaya. The problem being faced in this study is the amount of hoax news on social media that can affect the mindset and digital ethics of Generation Z. The method used is quantitative with data collection techniques by distributing data through a Google Form questionnaire and using information from previous literature, journals, online media and books. The results of the study reveal that the use of social media by Generation Z is in accordance with good digital ethics such as using social media to upload photos, send messages and for school and lecture activities. Generation Z also uses social media to see the latest information. However, if there is hoax news, Generation Z tends to check the truth. As a theoretical perspective a theory of uses and gratifications on digital media use to reveal this phenomenon.